2015
DOI: 10.1080/00949655.2015.1071375
|View full text |Cite
|
Sign up to set email alerts
|

An EM algorithm for estimating the destructive weighted Poisson cure rate model

Abstract: In this paper, an algorithm is developed to compute estimates for parameters in destructive weighted Poisson cure rate models. It is shown, analytically, the robustness of the procedure with respect to the maximization of the observed likelihood function. The approach allows a simple implementation of different distributions for non-destroyed concurrent causes. The performance of the method is evaluated through simulation studies and by analysing a real data set related to patients with malignant melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Since this pioneering work, few other researchers have proposed extensions of this destructive cure rate model. In this regard, interested readers may refer to Gallardo et al (2016) and Balakrishnan (2016, 2017); see also Cancho et al (2013) and Pal et al (2018). In the context of these aforementioned works on cure rate models and destructive cure rate models, the development of the expectation maximization (EM) algorithm or, simply, the direct numerical maximization of the log-likelihood function turns out to be the commonly used tools for maximum likelihood estimation of the model parameters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since this pioneering work, few other researchers have proposed extensions of this destructive cure rate model. In this regard, interested readers may refer to Gallardo et al (2016) and Balakrishnan (2016, 2017); see also Cancho et al (2013) and Pal et al (2018). In the context of these aforementioned works on cure rate models and destructive cure rate models, the development of the expectation maximization (EM) algorithm or, simply, the direct numerical maximization of the log-likelihood function turns out to be the commonly used tools for maximum likelihood estimation of the model parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of destructive cure rate models, Gallardo et al (2016) developed a variation of the EM algorithm, where they showed that the objective function to be maximized can be decomposed into simpler functions and each simple function can be maximized separately. Although this turned out to be an advantage over the EM algorithms developed by Balakrishnan (2016, 2017), the authors still had to depend on the profile likelihood technique, also called the grid search technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as developing the likelihood inference and finding the maximum likelihood estimates (MLEs) are concerned in the given context, the expectation maximization (EM) algorithm is a very popular technique. Interested readers may refer to Cancho et al (2013), Gallardo et al (2016), Pal and Balakrishnan (2017b), and Wiangnak and Pal (2018).…”
Section: Introductionmentioning
confidence: 99%
“…is expectation taken with respect to the Poisson pmf. Gallardo et al (2016) developed an EM algorithm based technique for the same model for estimating the parameters for the three special cases, viz., destructive length-biased Poisson, destructive exponentially weighted Poisson and destructive negative binomial cure models. An extension of this model was described by Borges et al (2012) by creating a correlation structure between the initiated cells using the generalized power series distribution.…”
Section: Introductionmentioning
confidence: 99%